Analisis Strategi Pemasaran Hmns Parfume Di Era Digital - Sahwa Lioni Ayu; Easter Tobing (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The rapid development of information technology and e-commerce transformation in Indonesia has significantly shifted consumer purchasing behavior, including within the fragrance industry. HMNS Parfume is a prominent Indonesian local fragrance brand that has successfully dominated the digital market despite the inherent challenge of selling products without direct sensory experiences (blind buy). This study aims to analyze the digital marketing strategies employed by HMNS Parfume across social media and e-commerce platforms, particularly TikTok Shop and Shopee, and their impact on consumer purchase decisions. A qualitative descriptive methodology was adopted, utilizing a literature review approach and content analysis. The findings reveal that HMNS's market success is driven by the integration of emotional branding strategies (spanning four key pillars: relationship, sensorial experience, imagination, and vision) alongside compelling narrative storytelling. The primary barrier of blind buying is effectively mitigated through detailed product descriptions, availability of sample discovery sets, interactive live-streaming features, and leveraging social proof via online customer reviews and User-Generated Content (UGC). Based on the SWOT analysis, HMNS holds a strong position due to research-backed product formulation and distinct brand storytelling, allowing the brand to capitalize on the surge of "local pride" trends and social commerce growth. To sustain long-term growth, the study recommends that HMNS strengthen its omnichannel presence through offline physical touchpoints to provide direct sensory experiences prior to online repurchases